2015
DOI: 10.1186/s13024-015-0002-2
|View full text |Cite
|
Sign up to set email alerts
|

APOE4 enhances age-dependent decline in cognitive function by down-regulating an NMDA receptor pathway in EFAD-Tg mice

Abstract: BackgroundAlzheimer’s disease (AD) causes progressive loss of memory and cognition, exacerbated by APOE4, the greatest genetic risk factor for AD. One proposed mechanism for apolipoprotein E (apoE) effects on cognition is via NMDAR-dependent signaling. APOE genotype-specific effects on this pathway were dissected using EFAD-transgenic (Tg) mice (5xFAD mice, that over-express human amyloid-beta (Aβ) via 5 familial-AD (FAD) mutations, and express human apoE), and 5xFAD/APOE-knockout (KO) mice. Previous data from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
66
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 136 publications
(160 reference statements)
6
66
0
Order By: Relevance
“…Consistent with this notion, we showed that astrocytic apoE4 expression enhances plaque-associated inflammatory responses, whereas increased levels of apoE3 suppress Aβ-driven neuroinflammation and ameliorates post-synaptic alteration. In addition, apoE isoforms have been shown to differentially regulate synaptic functions by multiple mechanisms, such as modulating the signaling function of post-synaptic receptors (Chen et al, 2010; Liu et al, 2015b). How expression of astrocytic apoE3 and apoE4 impacts synaptic functions and plasticity in the absence of amyloid pathology requires future investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this notion, we showed that astrocytic apoE4 expression enhances plaque-associated inflammatory responses, whereas increased levels of apoE3 suppress Aβ-driven neuroinflammation and ameliorates post-synaptic alteration. In addition, apoE isoforms have been shown to differentially regulate synaptic functions by multiple mechanisms, such as modulating the signaling function of post-synaptic receptors (Chen et al, 2010; Liu et al, 2015b). How expression of astrocytic apoE3 and apoE4 impacts synaptic functions and plasticity in the absence of amyloid pathology requires future investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Morris water maze (MWM) was conducted as described in [35] with slight modifications in three phases. The circular pool was 120 cm in diameter and 50 cm tall, and the circular escape platform was 10 cm in diameter.…”
Section: Methodsmentioning
confidence: 99%
“…In animals, reduced excitatory synaptic transmission/dendritic arborisation [74], reduced spine length/density [75, 76], and reduced synaptic markers [63] have been observed in apoE4-TR mice compared to apoE3-TR mice. Enhanced age-dependent cognitive decline in apoE4 accompanied by reduction in postsynaptic density 95 (PSD-95), drebrin and NMDA receptor subunits was also observed in amyloid mouse model when compared to apoE2 or apoE3 [77]. …”
Section: Impacts Of Apoe On Brain Pathophysiology In Admentioning
confidence: 99%